Posterior calcaneal spur length and angle are predictors of pain and functional limitation in insertional Achilles tendinopathy - Dinç, Mustafa; Soydemir, Ömer Cevdet; Karasu, Recep; Aykaç, Bilal; Bayrak, Hünkar Çağdaş (The European Research Journal, 2025)
Objectives: This study aimed to quantitatively evaluate the clinical impact of posterior calcaneal spur (PoCS) morphology, specifically spur length and inclination angle, in patients with insertional Achilles tendinopathy (IAT). Methods: This retrospective study analyzed 200 patients with symptomatic IAT who underwent standardized weight-bearing lateral ankle radiographs. Spur length and inclination angle were measured, and patients were stratified into nine subgroups based on three length categories (<5 mm, 5-10 mm, >10 mm) and three angle categories (<10°, 10-20°, >20°). Clinical outcomes were assessed using the Visual Analog Scale (VAS), American Orthopaedic Foot and Ankle Society (AOFAS) score, and Victorian Institute of Sport Assessment-Achilles (VISA-A) score. Kruskal-Wallis tests and multivariate linear regression analyses were used to evaluate associations between spur morphology and outcomes. Results: Both longer spurs (>10 mm) and steeper inclination angles (>20°) were significantly associated with worse clinical scores including higher VAS scores and lower AOFAS and VISA-A scores (P<0.001). Patients with spur lengths >10 mm and angles >20° had a mean VAS score of 7.22±0.65, VISA-A score of 49.72±2.54, and AOFAS score of 60.00±4.24, indicating greater pain and functional limitation. In contrast, patients with spur lengths <5 mm and angles <10° had lower VAS scores (5.18±0.82) and higher VISA-A (63.43±3.92) and AOFAS (72.57±4.33) scores, reflecting lower pain intensity and higher functional capacity (P < 0.001 for all). Regression analysis confirmed that spur length and angle were independent predictors of clinical outcome (P<0.001), while age, sex, and BMI were not statistically significant contributors (P>0.05). Conclusions: Spur morphology - specifically length and angle - has a measurable impact on symptom severity in IAT. Radiographic evaluation of PoCS morphology should be integrated into clinical decision-making for more tailored management.